Lost city of the Templars - Christopher, Paul (Signet novel, 2013)
When he and his crew uncover a five-hundred-year-old society hidden in the cauldron of the Amazon, John Holliday, trailed by hostile natives and an infamous tomb raider, comes face-to-face with the legendary Ark of the Covenant.